Synthesis and Characterization of New Palladium(II) Thiosemicarbazone Complexes and Their Cytotoxic Activity against Various Human Tumor Cell Lines - Wilfredo Hernández; Juan Paz; Fernando Carrasco; Abraham Vaisberg; Evgenia Spodine; Jorge Manzur; Lothar Hennig; Joachim Sieler; Steffen Blaurock; Lothar Beyer (Bioinorganic Chemistry and Applications)
The palladium(II) bis-chelate complexes of the type [Pd(TSC1-5)2] (6–10), with their corresponding ligands 4-phenyl-1-(acetone)-thiosemicarbazone, HTSC1 (1), 4-phenyl-1-(2′-chloro-benzaldehyde)-thiosemicarbazone, HTSC2 (2), 4-phenyl-1-(3′-hydroxy-benzaldehyde)-thiosemicarbazone, HTSC3 (3), 4-phenyl-1-(2′-naphthaldehyde)-thiosemicarbazone, HTSC4 (4), and 4-phenyl-1-(1′-nitro-2′-naphthaldehyde)-thiosemicarbazone, HTSC5 (5), were synthesized and characterized by elemental analysis and spectroscopic techniques (IR and 1H- and 13C-NMR). The molecular structure of HTSC3, HTSC4, and [Pd(TSC1)2] (6) have been determined by single crystal X-ray crystallography. Complex 6 shows a square planar geometry with two deprotonated ligands coordinated to PdII through the azomethine nitrogen and thione sulfur atoms in a cis arrangement. The in vitro cytotoxic activity measurements indicate that the palladium(II) complexes (IC50=0.01–9.87 μM) exhibited higher antiproliferative activity than their free ligands (IC50=23.48–70.86 and >250 μM) against different types of human tumor cell lines. Among all the studied palladium(II) complexes, the [Pd(TSC3)2] (8) complex exhibited high antitumor activity on the DU145 prostate carcinoma and K562 chronic myelogenous leukemia cells, with low values of the inhibitory concentration (0.01 and 0.02 μM, resp.).